Five Decades Since Prejudices and Antipathies - Mullender, Alec (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2025)
How has the evolution of both library classification and the critical classification field affected the legacy and relevance of one of its most celebrated works? Sanford Berman’s 1971 monograph Prejudices and Antipathies: A Tract on the LC Subject Heads Concerning People, while being by no means the first to critically assess the Library of Congress Subject Headings (LCSH), gained significant interest (both positive and negative) from the cataloguing community. Steven A. Knowlton’s 2005 follow-up article Three Decades Since Prejudices and Antipathies: A Study of Changes in the Library of Congress Subject Headings examined the impact of Berman’s book on the LCSH.In 2025, this paper returns to Berman’s book to follow up on both works. Through an analysis of trends across published critical classification literature of the past five decades—in particular in relation to the approach taken by the book to criticism of the Library of Congress and LCSH in comparison to other topics—this paper examines how the landscape of critical classification has changed and, through that, how perceived obstacles and goals have shifted in the half century since the publication of Berman’s book, in order to examine its place and legacy.